Geometric tuning of charge and spin correlations in manganite superlattices - Rogdakis, K. (2015)
We report a modulation of the in-plane magnetotransport in artificial manganite superlattice [(NdMnO3) n /(SrMnO3) n /(LaMnO3) n ] m by varying the layer thickness n while keeping the total thickness of the structure constant. Charge transport in these heterostructures is confined to the interfaces and occurs via variable range hopping. Upon increasing n, the interfacial separation rises, leading to a suppression of the electrostatic screening between carriers of neighboring interfaces and the opening of a Coulomb gap at the Fermi level (EF ). The high-field magnetoresistance (MR) is universally negative due to progressive spin alignment. However, at a critical thickness of n = 5 unit cells (u.c.), an exchange field coupling between ferromagnetically ordered interfaces results in positive MR at low magnetic field (H). Our results demonstrate the ability to geometrically tune the electrical transport between regimes dominated by either charge or spin correlations.